Great expectations: A tale of two transitions - Daniele Girardi; Roberto Veneziani; Susanne Wengle (Queen Mary University of London, School of Economics and Finance, 2023)
Over a quarter of the world's population lives in economies that have undertaken transitions from central planning to market economies. These transitions entail far-reaching and complex changes in social, economic and political institutions and have had widely divergent outcomes. Important strands of literature have emphasised the strategic complementarities that characterise the transition process in both the economic and political realms. Contrary to a widespread assumption, market-supporting institutions do not necessarily arise when assets are privatised in a highly unstable and uncertain environment; in fact, multiple equilibria emerge and expectations may play a key role in equilibrium selection. In this paper, we survey the vast empirical literature on transition economies in order to provide evidence on the correlation between expectations at the beginning of transition and success of the transition process. We provide the first comprehensive survey of the literature on agents' subjective perceptions of transitions' paths.
Keywords: D73; P31; P26; K42; 330; Transition; expectations; multiple equilibria; property rights